Resting Cardiac Power Predicts Adverse Outcome in Heart Failure Patients With Preserved Ejection Fraction: A Prospective Study - Wang, Shiqi; Chen, Aiqi; Duan, Xiaokai (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: We sought to explore the significance of resting cardiac power/mass in predicting adverse outcome in patients with heart failure with preserved ejection fraction (HFpEF). Methods: This prospective cohort study included patients with HFpEF and without significant valve disease or right ventricular dysfunction. Cardiac power was normalized to left ventricular (LV) mass and expressed in W/100g of LV myocardium. Multivariate Cox regression analysis was used to evaluate the association between resting cardiac power/mass and composite endpoint, which included all-cause mortality and heart failure (HF) hospitalization. Results: A total of 2089 patients were included in this study. After an average follow-up of 4.4 years, 612 (29.30%) patients had composite endpoint, in which 331 (15.84%) died and 391 (18.72%) experienced HF hospitalization. In multivariate Cox regression analysis, resting power/mass <0.7 W/m2 was independently associated with composite endpoint, all-cause mortality, cardiovascular mortality and HF hospitalization, with hazard ratios (HR) of 1.309 [95% confidence interval (CI): 1.108–1.546, P=0.002], 1.697 (95%CI: 1.344–2.143, P<0.001), 2.513 (95%CI: 1.711–3.689, P<0.001), and 1.294 (95%CI: 1.052–1.592, P=0.015), respectively. For composite endpoint, cardiovascular mortality and HF hospitalization, the C statistic increased significantly when incorporating resting cardiac power/mass into a model with established risk factors. For composite endpoint, the continuous net reclassification index after adding resting cardiac power/mass in the original model with N-terminal pro-brain natriuretic peptide was 13.1% (95%CI: 2.9%–21.6%, P=0.007), and the integrated discrimination index was 1.9% (95%CI: 0.8%–3.2%, P<0.001). Conclusions: Resting cardiac power determined by non-invasive echocardiography is independently associated with the risk of adverse outcomes in HFpEF patients and provides incremental prognostic information. Keywords: Cardiac power, heart failure with preserved ejection fraction, echocardiography, prognosis, adverse outcome.